"Guidewire Intravenous Catheter Systems Do Not Improve First-Pass Success Rates for Peripheral Access When Placed By Army Combat Medics (68W) in a Pre-hospital Setting." A Prospective, Randomized Controlled Trial with Crossover Study Design. Issue 11 (24th May 2018) - Jin, Lisa M; Medeck, Sarah; Ruley, James; Riddle, Mark; Aden, James
Abstract: Introduction: This study was completed to determine if guidewire catheters improve first-pass success and time of placement for peripheral intravenous access. In the military, 21% of casualties from the battlefield arrive to a medical facility in hemorrhagic shock. The importance of successful and timely intravenous placement is crucial in the initial steps of preventing this condition. Multiple studies and reviews have shown that initial first-pass success rates for pre-hospital intravenous placement have been as low as 40%, and an average success rate of 81% when completed by paramedics or similarly skilled personnel. In an attempt to replicate or improve these rates, we proposed to study placement success rates by active duty military combat medics. We hypothesized that there would be no difference in first-pass success rates when using either a standard or guidewire catheter. Materials and Methods: This study was a prospective, randomized, controlled trial with a crossover study design comparing the Accucath 18-gauge guidewire catheter to the standard 18-gauge peripheral intravenous catheter. The study included 93 1st Cavalry Division Army Combat Medics. Participants were voluntarily enrolled and consented on an individual basis. Each participant paired with a partner of their choice and acted as their own control. All supplies were laid out for the participants with the catheters randomly selected for either arm of the patient. The subjects were allowed to choose which catheter they would be tested on first. Times were recorded for only successful attempts. Results: The guidewire catheter was not proven to have a higher cannulation rate, achieving only a 44% success rate versus 66% in the standard catheter group, as well as averaging 42 seconds longer to obtain successful cannulation versus the standard catheter. Interestingly, it was observed that the greater the time in service, there was an increased success rate with the guidewire catheter that was not noted with the standard catheter. Conclusions: There was not a statistically significant improvement in the first-pass success rate of intravenous placement with the use of the guidewire catheter when compared with the standard-issue catheter. With these results, we cannot recommend the guidewire catheter to be used in leu of the standard catheter. Further studies might show improvement if subjects are allotted increased practice and familiarity with the new guidewire device.